Women of different generations living with HIV: social representations about sexuality - Suto, Cleuma Sueli Santos; Coelho, Edméia de Almeida Cardoso; Paiva, Mirian Santos; Porcino, Carle; Cabral, Letícia da Silva; Marques, Sérgio Corrêa (Revista da Escola de Enfermagem da USP, 2020)
Objective To analyze the social representations of women diagnosed with HIV about their sexuality considering generational characteristics. Method Qualitative study, carried out with women who participated through interviews. The constituted corpus was processed by the Iramuteq software. The analysis was based on the Theory of Social Representations. Results A total of 39 women participated in the study, aged between 18-76 years old and most of them had high school education, evoked the terms ‘people’ (301), ‘partner’ (277), ‘children’ (249), ‘virus’ (275) and ‘want’ (216). The younger ones accept to reveal and/or ‘tell’ about their condition to their partner(s) and family members, an aspect that is not revealed in the statements of women of other ages. For women aged 45 and over, children occupy a prominent place and for the older adults, the centrality of representation referred to self-censorship and maintaining the victim/guilty game. Conclusion This study made it possible to identify processes of anchoring sexualities in terms of what ‘cannot be revealed’ beyond the family context. It should be noted that the elements ‘sex’, intercourse’ conceived by common sense as a synonym for sexuality, regardless of generation, had low frequency.